Kepastian Hukum Program Legislasi Kabupaten/Kotaterhadap Pembangunan Hukum Di Daerah - Ansarullah Ansarullah; Purnama Eddy; Efendi Efendi (Jurnal Suara Hukum, 2022)
The Formulation of Qanun through a legislation program (Prolek) implemented in a planned, integrated, and systematic with the aim to realize certainty of legal development in the region. The process of drafting the legislation program is carried out not in accordance with the planning and scale of priorities that have been set so as not to provide legal certainty to the priority and legal development in the region. This study uses normative juridical methods with a statue approach and conceptual approach. In addition, to determine the aspects that cause the lack of legal certainty, this study also uses empirical juridical methods. The establishment of the Local Legislation Program has not provided legal certainty because Qanun Aceh No. 5 of 2011 on The Procedure of Formation of Qanun has not set concretely on the scale of priorities that form the basis of the urgency of the establishment of a qanun. In addition, the District House of Representative (DPRK) given the function of legislation in the region does not yet have a preference for the field of legislation so that the process of legislation can not be completed as planned. In addition, DPRK given the function of legislation in the region does not have a preference for the field of legislation so the process of legislation can not be completed according to the planning. In realization the legal certainty of the local legislation program against legal development in the region there needs to be concrete regulatory efforts in the provisions of Qanun Aceh No. 5 of 2011 relating to determining the scale of priorities as well as changing the mindset of the DPRK in the field of legislation by making it part of the priority function. Keywords: Legal Certainty, Legislation Program, Legal Development